JEJAK SANG PENYAIR PERSIA: CORAK SASTRA SUFISTIK JALALUDDIN MUHAMMAD MAULAVI DALAM KARYANYA â€œMATSNAWIâ€ - Ahmadi, Rizqa (Jurnal CMES, 2013)
his paper analyzes sufistic literature of Jalaluddin Muhammad Maulavi throughhis works Matsnawi al-Maâ€Ÿnawi. Based on analyze, this book not only contain basicprinciples of religion, but also contain other universal values.Â  His view about unity ofexistence (wahdatul wujud) is the character of his thought about live and the existence ofGod. Love can deliver human in real peace and happiness. Besides, Maulavi has his ownview about woman. Woman is people bring in positive and negative energy. The Sufisdescribes woman as creature having same ability with man. Although in certain phrase,he dramatizes woman position as despicable creature.